A PERFORMANCE-BASED APPROACH TO AIRSPACE OPTIMIZATION USING WIND-OPTIMAL TRACKS NETWORK IN HO CHI MINH FIR - Ngoc Hoang Quan NGUYEN; Minh Hoang LE; Trinh Binh DINH; Phuc Ky NGUYEN; Thu Thao NGUYEN; Toan Thinh LE; Van Tien Son NGUYEN; Hoang Vu NGUYEN (Scientific Journal of Silesian University of Technology. Series Transport, 2025)
With the fast-paced development of the aviation industry, air traffic is also increasing, leading to the problem of how to control the traffic safely, and effectively, and increase the capacity of airspace. Therefore, numerous approaches have been taken to cope with this, including optimal models - an effective approach to addressing airspace congestion issues worldwide. However, the application of these models in Vietnam remains relatively limited. In this research, we aim to address the issue of airspace congestion and how to enhance safety and efficiency by developing an algorithm capable of automatically detecting and resolving conflicts. This is achieved by adjusting the entry time and flight level (FL) of aircraft operating within the Wind-Optimal Track Network (WOTN) model that we have developed for the Ho Chi Minh Flight Information Region (HCM FIR). The research contributes to the advancement of air traffic management (ATM) systems, particularly in the context of HCM FIR, minimizing air traffic controller (ATC) workload, and offering valuable insights for enhancing operational efficiency and safety in the airspace.